Unsafe reasoning: a survey - Faria, Paulo (DoisPontos, 2009)
Judgments about the validity of at least some elementary inferential patterns (say modus ponens) are a priori if anything is. Yet a number of empirical conditions must in each case be satisfied in order for a particular inference to instantiate this or that inferential pattern. We may on occasion be entitled to presuppose that such conditions are satisfied (and the entitlement may even be a priori), yet only experience could tell us that such was indeed the case. Current discussion about a perceived incompatibility between content externalism and first-person authority exemplifies how damaging the neglect of such empirical presuppositions of correct reasoning can be. An externalistic view of mental content is ostensibly incompatible with the assumption that a rational subject should be able to avoid inconsistency no matter what the state of her empirical knowledge may be. That fact, however, needs not be taken (as it often is) as a reductio of externalism: alternatively, we may reject that assumption, adding to the agenda of a philosophical investigation of rationality an examination of the vicissitudes of logical luck. I offer an illustration and defense of that alternative. Raciocínio inseguro: um estudo - Juízos sobre a validade de pelo menos alguns padrões inferenciais elementares (digamos modus ponens) são a priori se alguma coisa é. No entanto, uma série de condições empíricas devem, em cada caso, ser satisfeitas para que uma inferência particular infera este ou aquele padrão inferencial. Podemos até mesmo ter o direito de pressupor que tais condições estão satisfeitas (e o direito pode até ser a priori), mas apenas a experiência poderia nos dizer que esse era de fato o caso. A discussão atual sobre uma incompatibilidade percebida entre externalismo de conteúdo e autoridade em primeira pessoa exemplifica como pode ser prejudicial a negligência de tais pressupostos empíricos de raciocínio correto. Uma visão externa do conteúdo mental é ostensivamente incompatível com a suposição de que um sujeito racional deve ser capaz de evitar inconsistências, não importa qual seja o estado de seu conhecimento empírico. Esse fato, no entanto, não deve ser tomado (como muitas vezes é) como um reductio do externalismo: alternativamente, podemos rejeitar essa suposição, adicionando à agenda de uma investigação filosófica da racionalidade um exame das vicissitudes da sorte lógica. Ofereço uma ilustração e defesa dessa alternativa.